Deep taxon sampling reveals the evolutionary dynamics of novel gene families in Pristionchus nematodes - Prabh, Neel; Roeseler, Waltraud; Witte, Hanh; Eberhardt, Gabi; Sommer, Ralf J.; Rödelsperger, Christian

(untitled) (Genome Research, 2018)
The widespread identification of genes without detectable homology in related taxa is a hallmark of genome sequencing projects in animals, together with the abundance of gene duplications. Such genes have been called novel, young, taxon-restricted, or orphans, but little is known about the mechanisms accounting for their origin, age, and mode of evolution. Phylogenomic studies relying on deep and systematic taxon sampling and using the comparative method can provide insight into the evolutionary dynamics acting on novel genes. We used a phylogenomic approach for the nematode model organism Pristionchus pacificus and sequenced six additional Pristionchus and two outgroup species. This resulted in 10 genomes with a ladder-like phylogeny, sequenced in one laboratory using the same platform and analyzed by the same bioinformatic procedures. Our analysis revealed that 68%–81% of genes are assignable to orthologous gene families, the majority of which defined nine age classes with presence/absence patterns that can be explained by single evolutionary events. Contrasting different age classes, we find that older age classes are concentrated at chromosome centers, whereas novel gene families preferentially arise at the periphery, are weakly expressed, evolve rapidly, and have a high propensity of being lost. Over time, they increase in expression and become more constrained. Thus, the detailed phylogenetic resolution allowed a comprehensive characterization of the evolutionary dynamics of Pristionchus genomes indicating that distribution of age classes and their associated differences shape chromosomal divergence. This study establishes the Pristionchus system for future research on the mechanisms that drive the formation of novel genes.